Instrumentos de apoio financeiro específicos a empresas localizadas em arranjos produtivos locais: um estudo de caso do APL de Nova Friburgo - Carvalho, Marco Aurelio Duarte de (2005)
In the last decade, the debate concerning more adequate means of promoting social and economic development, through policies of firm supporting, has been gaining strength. Among several means of support, there is one that addresses issues related to credit and funding. At the same time, interest on the phenomenon of firm agglomeration, known by clustering, is increasing, as well as one of its advantages - facilitating the development and strengthening of its firms. Additionally, there can be spotted advantages on clustering that allow tailoring financial instruments, specifically to firms in it, based on collective solutions, with better conditions. This dissertation focuses on how the capture of these opportunities is being done, in the presence of specific financial products to Brazilian clusters. The present analysis is conducted from the cluster located in Nova Friburgo and Region, specialized in women underwear. This study sought to capture advantages from three main collective solutions: information systems, guarantees systems, alternative funding. These solutions address to the following issues: information asymmetries, absence of guarantees from the credit taker, limited sources of funding. Semi-structured interviews were made with members of the cluster, when it was possible to identify that the capture of advantages is in its early stages, being limited by other issues, such as: adequate degree of human capital, governance framework and process inefficiencies.